Bile salt induced solubilization of methylene blue: Study on methylene blue fluorescence properties and molecular mechanics calculation - Susithra Selvam; Ivy Sarkar (Elsevier, 2017)
Methylene blue (MB) is a hydrophobic drug molecule, having importance both as a staining reagent and pharmaceutical agent. MB is strongly fluorescent, with an emission peak at 686 nm (λex 665 nm). In the study, the possibility of MB as an extrinsic fluorophore to study the micellization behavior of bile salts (BSs) was carried out. Since BSs are drug delivery systems, the solubilization of hydrophobic MB drug molecule by BSs was achieved and the nature of association of MB with BS media, namely sodium cholate (NaC) and sodium deoxycholate (NaDC) was evaluated. Change in the photophysical properties of MB is monitored through fluorescence intensity and fluorescence anisotropy at emission peak, 686 nm of MB. Molecular mechanics calculations were carried out to evaluate the MB-BS association. The estimated heat of formation, ΔHf values are -625.19 kcal/mol for MB-NaC and -757.48 kcal/mol for MB-NaDC. The photophysical study also revealed that MB reports the step-wise aggregation pattern of BSs media, as an extrinsic fluorescence probe.